Ovarian Fragmentation and AKT Stimulation for Expansion of Fertile Lifespan - Vo, Kim Cat Tuyen; Kawamura, Kazuhiro (Frontiers in Reproductive Health, 2021)
Since the first baby was born after conception using in vitro fertilization in 1978, the female infertility treatment has been well developed and yielded successful outcomes. However, successful pregnancies for patients with premature ovarian insufficiency and diminished ovarian reserve is still difficult and diverse strategies and therapies have been suggested to improve the chances to have their genetically linked offspring. Recent studies demonstrated that the activation Akt pathway by using a phosphatase and tensin homolog enzyme inhibitor and a phosphatidylinositol-3 kinase stimulator can promote the growth dormant primordial follicles in both mice and human ovaries. Subsequent researches suggested that fragmentation of the ovarian cortex into small cubes changed cytoskeletal actin dynamics and disrupted the Hippo signaling pathway, leading to increased expression of downstream growth factors and secondary follicle growth. Based on the combination of ovarian fragmentation and Akt stimulation, the in vitro activation (IVA) approach has resulted in successful follicle growth and live births in patients with premature ovarian insufficiency. Using the approach with disruption of Hippo signaling only was also shown to be effective for treating poor ovarian responders with diminishing ovarian reserve, including advanced age women and cancer patients undergoing sterilizing treatments. This review aims to summarize the effectiveness of ovarian fragmentation and Akt stimulation on follicle growth and the potential of IVA in extending female fertile lifespan.